Intratumor microbiome-derived butyrate promotes chemo-resistance in colorectal cancer - Linsheng Xu; Linsheng Xu; Bingde Hu; Jingli He; Xin Fu; Na Liu (Frontiers in Pharmacology)
IntroductionColorectal cancer (CRC) is a leading cause of cancer-related mortality globally. Although tumor immunotherapy is widely recognized for treating unresectable CRC, challenges such as ineffective immunotherapy and drug resistance remain prevalent. While intratumor microbiome-derived butyrate has been implicated in promoting lung cancer metastasis, its role in CRC chemoresistance is not well understood. This study aimed to explore the relationship between intratumor butyrate and chemoresistance in CRC.MethodsWe performed a comprehensive analysis of the microbiome composition in CRC patients with varying resistance-free survival (RFS) durations, utilizing 16S rRNA sequencing. Furthermore, we assessed the prognostic significance of circulating microbiome DNA (cmDNA) and examined the effects of exogenous butyrate supplementation on the chemosensitivity of CRC cell lines.ResultsOur 16S sequencing analysis revealed a reduction in microbial diversity within tumor samples of patients with resistance, as indicated by metrics such as observed taxonomic units, Shannon, and Simpson indices. Notably, Roseburia and Fusobacteria emerged as prominent biomarkers for the resistance group, whereas Bifidobacterium, Helicobacter, and Akkermansia were identified as biomarkers for the non-resistant group. Utilizing a Lasso regression model, we identified six genera-Roseburia, Helicobacter, Gardnerella, Flavonifractor, Coprococcus, and Anaerostipes-that significantly correlated with recurrence-free survival. Furthermore, both the intratumor microbiome signature and circulating microbiome DNA were effective in accurately predicting CRC resistance. Experimental assays, including CCK8 and wound-healing, demonstrated that intratumor microbiome-derived butyrate enhances the proliferation and migration of HCT15 cells in a time- and concentration-dependent manner. Cell survival analysis further indicated that butyrate treatment significantly increased the IC50 value, suggesting heightened drug resistance in HCT15 cells. Mechanistically, this resistance was attributed to butyrate’s activation of the PI3K-AKT signaling pathway.ConclusionOur results suggest that intratumor microbiome-derived butyrate contributes to chemoresistance in colorectal cancer, highlighting the potential prognostic and therapeutic significance of the intratumor microbiome.